Exploring Reform Options in Functional Assignment - Ferrazzi, Gabriele (World Bank, Washington, DC, 2017)
Considerable challenges remain in functional assignment in Indonesia - some introduced by the recent revisions, during the second round of reform in the period 2004-2007. The Government of Indonesia (GoI) has accepted the offer from donors to undertake a study to delve more deeply into the progress made to date, the challenges that remain, and the opportunities to fashion a more robust, effective and stable assignment of functions. The study aims to help the GoI and donors in exploring new avenues for reform in this field. The term functional assignment in the study denotes a broad concept that captures the overall architecture of roles between levels of government and the specific construction of functions. The robustness of functional assignment is seen to derive from the judicious choice of elements suited to the local context, particularly how these elements come together to form a sound and consistent architecture. In assessing functional assignment, the study made use of academic and other stakeholder views on both substantive issues and the capacity development approach needed to develop a policy network in this field in the future. The possible supporting role of donors is also indicated, within the discussion of each issue in the main part of the report, and in condensed form at the end of this summary.